A novel water vapour carrier (WVC) model for the transportation of low concentration dissolved gas through the membrane - Rosalam Sarbatly; Duduku Krishnaiah; Yeo, Kiam Beng (Universiti Malaysia Sabah, 2010)
No Abstract